CHILD FEEDING PATTERN DURING TRANSITIONAL PERIOD (6-8 MONTHS) IN JONGGAT SUB DISTRICT, CENTRAL LOMBOK, WEST NUSA TENGGARA - Karina Rahmadia Ekawidyani; Lindawati Wibowo; Lina Rospita; Luh Ade Wiradnyani; Manjilala Manjilala; Sitha Dwita Putriani; Ragil Marini (Food and Nutrition Society of Indonesia, 2015)
ABSTRACTThe objective of this study was to assess child feeding knowledge and practice in transitional period (6-8 months), mother’s information exposure and the functioning of the health system in delivering complementary feeding programs. A cross sectional study was done to 175 children aged 6-8 months at 12 villages in Jonggat Sub-district, Lombok. Structured interview to the mothers, 24 hour recalls, and in-depth interview to the cadres of Integrated Health Posts were used throughout the study. Most mothers had poor knowledge and practice on child feeding (68.0% and 75.4%, respectively). Almost all children had received complementary food (98.9%), but only less than a half children were introduced to complementary food at the appropriate age i.e. 6 months (45.7%). Only few children had good dietary diversity i.e. ≥ 4 food type in the previous day (6.9%). More than half of the mothers (52%) were exposed to information related to child feeding practice. The sources of information mostly were from health officers, cadres, mother and child health book and printed media (e.g. newspaper and magazine). The local health staff and cadres had basic knowledge on child feeding programs but the practice was not adequate. Mother’s knowledge and practice on child feeding within the transitional period in Jonggat sub-district was poor. The health system was not functioning well in delivering complementary feeding programs.Keywords: cadres, child feeding pattern, complementary feeding programsABSTRAKPenelitian ini bertujuan untuk mengkaji pengetahuan dan praktek pengasuhan makan pada anak selama masa transisi (6-8 bulan), sumber informasi ibu, dan keberhasilan sistem kesehatan dalam program MP-ASI. Cross sectional study dilakukan dengan subjek 175 anak usia 6-8 bulan di 12 desa di Kecamatan Jonggat, Lombok. Pengumpulan data dilakukan dengan wawancara terstruktur kepada ibu, food recall, dan wawancara mendalam kepada kader Pos Pelayanan Terpadu (Posyandu). Sebagian besar ibu memiliki pengetahuan (68,0%) dan praktek (75,4%) pengasuhan makan anak yang rendah. Hampir seluruh anak sudah menerima MP-ASI (98,9%), tetapi kurang dari separuh anak menerima MP-ASI pada umur yang sesuai yaitu enam bulan (45,7%). Hanya sedikit anak (6,9%) yang memiliki skor keanekaragaman pangan baik, yaitu makan >4 jenis pangan pada hari kemarin. Sebesar 52% ibu sudah terpapar dengan informasi mengenai praktek pengasuhan makan anak. Sumber informasi paling banyak berasal dari petugas kesehatan, kader, buku Kesehatan Ibu dan Anak (KIA), dan media cetak. Petugas kesehatan setempat dan kader memiliki pengetahuan dasar mengenai program MP-ASI tetapi prakteknya masih kurang baik. Pengetahuan ibu dan praktek pengasuhan makan anak pada masa transisi di Kecamatan Jonggat masih kurang. Sistem kesehatan tidak berfungsi dengan baik dalam melaksanakan program MP-ASI.Kata kunci: kader, pola asuh makan anak, program MP-ASI